2023
DOI: 10.1002/anie.202301836
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific Synthesis of Enantiopure [6]Helicene Containing a Seven‐Membered Ring and [7]Helicene by Acid‐Promoted Stepwise Alkyne Annulations of Doubly Axial‐Chiral Precursors**

Abstract: Enantiopure [6]helicene containing an embedded seven‐membered ring and carbo[7]helicene (>99 % ee) with opposite helicity were simultaneously and quantitatively (>99 %) synthesized with a perfect stereospecificity through stepwise acid‐promoted intramolecular alkyne annulations of doubly axial‐chiral cyclization precursors. The helical handedness of the [6]‐ and [7]helicenes was fully stereocontrolled by the doubly axial chirality of the precursors as a result of complete axial‐to‐helical chirality transfer. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 89 publications
0
27
1
Order By: Relevance
“…In 2023, Yashima's group enantioselectively synthesized [6]helicenes 15 (>99 % ee ) containing a seven‐numbered ring and [7]helicenes 16 (>99 % ee ) from doubly axial‐chiral precursors in totally 99 % yield (Figure 6). [11] The results indicated that the acid‐promoted intramolecular alkyne annulations was stepwise and one hexagon was formed at first. This study once again proved that certain chiral precursors have the capability to produce helical molecules with a high enantiopurity.…”
Section: Enantioselective Synthesis Of Helicenesmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2023, Yashima's group enantioselectively synthesized [6]helicenes 15 (>99 % ee ) containing a seven‐numbered ring and [7]helicenes 16 (>99 % ee ) from doubly axial‐chiral precursors in totally 99 % yield (Figure 6). [11] The results indicated that the acid‐promoted intramolecular alkyne annulations was stepwise and one hexagon was formed at first. This study once again proved that certain chiral precursors have the capability to produce helical molecules with a high enantiopurity.…”
Section: Enantioselective Synthesis Of Helicenesmentioning
confidence: 99%
“…In 2023, Martín's group generated bilayer [9]helical nanographene 51 and [11]helical nanographene 52 (Figure 22) with 4 step reactions in overall yield as 11.2 % and 16.1 %, respectively. [27] The UV-vis absorption spectra of 50-52 show peaks at 569, 557 and 518 nm, respectively.…”
Section: π-Extended [N]helicenementioning
confidence: 99%
“…In recent years, a number of novel nonbenzenoid PAHs have been synthesized either in solutions [2] or on metal surfaces [3] . The remarkable synthetic achievements have enabled extensive investigations of the properties of these novel compounds, such as (anti)aromaticity, [4] open‐shell characters, [2g,5] and chiroptical responses [2b,u,6] . Furthermore, as exemplified by azulene derivatives, [7] the optoelectronic applications of nonbenzenoid PAHs have also been demonstrated, e.g.…”
Section: Figurementioning
confidence: 99%
“…[21] This reaction has also been used to assemble S-doped [22,23] and Ndoped nanographenes, [24] and, more recently, for the construction of helicenes. [25][26][27][28] Alkyne benzannulation occurs at the free position adjacent to the biaryl linkage leading to the formation of new rings of various sizes. Depending on the conditions and the catalyst used in the reaction, 5-, 6-and 7membered rings can be formed through 5-exo-dig, 6-endo/ exo-dig and 7-endo-dig ring closure mechanisms, respectively (Figure 1a).…”
Section: Introductionmentioning
confidence: 99%
“…Among several emblematic examples, a spectacular illustration concerns the synthesis of a polymeric graphene nanoribbon by Chalifoux and co‐workers [21] . This reaction has also been used to assemble S‐doped [22,23] and N‐doped nanographenes, [24] and, more recently, for the construction of helicenes [25–28] . Alkyne benzannulation occurs at the free position adjacent to the biaryl linkage leading to the formation of new rings of various sizes.…”
Section: Introductionmentioning
confidence: 99%